2022
DOI: 10.1136/jnnp-2021-327864
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ as a biomarker for predicting Aβ-PET status in Alzheimer’s disease:a systematic review with meta-analysis

Abstract: ObjectiveAmyloid-β positron emission tomography (Aβ-PET) scan has been proposed to detect amyloid-β (Aβ) deposition in the brain. However, this approach is costly and not ideal for the early diagnosis of Alzheimer’s disease. Blood-based Aβ measurement offers a scalable alternative to the costly or invasive biomarkers. The aim of this study was to statistically validate whether plasma Aβ could predict Aβ-PET status via meta-analysis.MethodsWe systematically searched for eligible studies from PubMed, Embase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…3,4 The core blood biomarkers of AD include Aβ42 (or Aβ42/40 ratio), phosphorylated tau181 (p-tau181), neurofilament light chain (NfL), and total tau (Ttau), which reflect Aβ pathology, tau pathology, and neuronal damage, respectively. 5,6 Various experimental results have shown that lower plasma Aβ42/Aβ40 ratio was associated with higher amyloid cortical burden, 7,8 faster Aβ accumulation rates, 9 greater cognitive declines, 10,11 and increased risk of developing AD dementia at follow-up. 12 Other research suggested plasma p-tau181 reflected changes in hyperphosphorylated tau in the brain in Aβ+ individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The core blood biomarkers of AD include Aβ42 (or Aβ42/40 ratio), phosphorylated tau181 (p-tau181), neurofilament light chain (NfL), and total tau (Ttau), which reflect Aβ pathology, tau pathology, and neuronal damage, respectively. 5,6 Various experimental results have shown that lower plasma Aβ42/Aβ40 ratio was associated with higher amyloid cortical burden, 7,8 faster Aβ accumulation rates, 9 greater cognitive declines, 10,11 and increased risk of developing AD dementia at follow-up. 12 Other research suggested plasma p-tau181 reflected changes in hyperphosphorylated tau in the brain in Aβ+ individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental results have shown that lower plasma Aβ42/Aβ40 ratio was associated with higher amyloid cortical burden, 7 , 8 faster Aβ accumulation rates, 9 greater cognitive declines, 10 , 11 and increased risk of developing AD dementia at follow‐up. 12 Other research suggested plasma p‐tau181 reflected changes in hyperphosphorylated tau in the brain in Aβ+ individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have shown that plasma biomarkers could predict disease stage and that integrating multiple plasma biomarkers could improve prediction accuracy ( Palmqvist et al, 2021 ; West et al, 2021 ; Cheng et al, 2022 ). In the present study, we investigated the prediction ability for disease stages of integrating plasma and urine biomarkers compared to using plasma biomarkers alone, revealing that combining all biomarkers could improve prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…found that Aβ oligomerization was significantly higher in AD patients than in normal people. Plus, the high correlations between Aβ oligomerization levels and other AD biomarkers, such as phosphorylated tau protein (pTau), amyloid positron emission tomography (PET) imaging, CSF biomarkers for Aβ42, total tau, and brain magnetic resonance imaging (MRI) were confirmed in many studies (Choi et al, 2021;Cheng et al, 2022).…”
Section: Multimer Detection System-oligomerized Amyloid Beta (Mds-oaβ)mentioning
confidence: 96%
“…To reduce the amount of lab workload and accelerate the SILK studies, Mawuenyega et al (2013) developed an efficient and specific quantitative isoform characterization and kinetics method. Plenty of studies adopting the IP-MS method elucidated that plasma Aβ42 concentration and Aβ42/Aβ40 rate are promising biomarkers for predicting Aβ status in individuals (Portelius et al, 2006(Portelius et al, , 2015Ovod et al, 2017;Cheng et al, 2022). Furthermore, immunoprecipitation together with SampleStream mass spectrometry (SampleStream-MS) was established.…”
Section: Immunoprecipitation-mass Spectrometrymentioning
confidence: 99%